(untitled) (Perioperaciina Medicina, 2024)
Trauma is a leading cause of death in people younger than 40 years, and on the third place after cardiovascular and oncological disease overall. Chest trauma is a fi nding in up to 60 % of patients with multiple trauma and has a mortality rate as high as 20–25 %. Rib fractures are the most common fi ndings in patients with thoracic trauma with mortality rates among hospitalised patients between 10 and 22 %. The mortality rate is higher in elderly patients and patients with flail chest. The incidence of pneumonia in the elderly population with three to four and more than six rib fractures is 31 % and 51 %, respectively. Pain due to rib fractures is challenging to manage but effective analgesia reduces hypoventilation, promotes deep breathing, sufficient coughing, clearance of secretions, and better adherence to chest physiotherapy. Th erefore, high-quality analgesia is not only increasing patient comfort but also is very important in preventing complications and improving the outcome. Th e purpose of this review is to analyse the modern literature regarding pain management for a patient with rib fractures and extract the best evidence-based practice.